Excellence in Malaysian universities: Senior academics in public and private institutions discuss this notion - Steele, G.S. (Universiti Putra Malaysia, 2014)
An article from the Times Higher Education inspired this investigation into the perception of university excellence in Malaysian universities with senior academics. Focus group discussions took place in two private and two public universities with random keywords supplied to facilitate the discussions. Discourse analysis of the transcripts of the tape-recorded discussions revealed the academics in private universities tended to use more lexical items associated with industry and liberal market ideologies, such as "employability" and "brand," which conform to a newly-identified description of the research university as an academic entrepreneurial paradigm. By contrast, public university academics emerged as intellectual purists, with references to "curiosity-driven research," "academic freedom," and "commitment" to the transfer of knowledge, in their discussions. Such terms are reflective of more traditional notions of our oldest social institution, the university. Â© Universiti Putra Malaysia Press